Firms and early retirement: Offers that one does not refuse - Lutz Bellmann; Florian Janik (Institute for the Study of Labor (IZA), 2007)
According to the Hutchens (1999) model, early retirement is not explained as a result of maximizing expected individual utility but rather as a demand-side phenomenon arising from a firm's profit-maximizing behaviour. Firms enter into contracts with their employees that include clauses about early retirement. In response to demand or technological shocks, workers receive retirement offers from their employers which cannot be rejected by rational actors. Using the IAB Establishment Panel 2003-2006, the relationship between indicators of demand and technological shocks and the incidence and amount of early retirement is analysed. The results provide general support to the Hutchens model.
Keywords: 330; Flexible Altersgrenze; Arbeitsvertrag; Implizite Kontrakte; Arbeitsnachfrage; Technischer Fortschritt; Schock; Deutschland